Mathematical Representation Ability and Student Confidence through Auditory Intellectually Repetition - Nia Jusniani; Eka Firmansyah (Program Studi Tadris Matematika IAIN Salatiga, 2021)
The purpose of this study is to determine the difference in the ability of mathematical representation of students students' confidence who use the auditory intellectually repetition learning model with students who use the usual learning model. This research is used quantitative analysis with the Quasi-Experimental Design method. The research design used is a nonequivalent control group design. This study's population was grade VII students academic year 2018/2019. The samples in this study were selected using a purposive sampling technique with grade VII-1 as an experimental class of 30 students and grade VII-2 as a Control class with 30 students. Experimental classes follow learning with auditory Intellectually Repetition models, and control classes follow conventional learning. The research analysis results showed that there were differences in the ability of mathematical representation of students using auditory intellectual repetition learning models with students using ordinary learning models. There is a difference in the confidence of students who use Auditory Intellectually Repetition learning with students who use the usual learning model.